Brain-body interactions underlying the association of loneliness with mental and physical health. (September 2020) - Quadt, Lisa; Esposito, Giulia; Critchley, Hugo D.; Garfinkel, Sarah N.
Highlights: Loneliness is linked with increased risk of morbidity and mortality. Higher rates of loneliness are observed in specific patient groups. Isolation leads to the activation of a patterned physiological and neural response. The prolonged activation of this response is linked with biopsychosocial morbidity. This association is framed in a mechanistic model of predictive social allostasis. Abstract: Loneliness can be operationalized as the actual or perceived absence of those social relationships that serve to meet basic emotional needs. In contrast to solitude, a chosen state of being without company, loneliness is associated with negative affect and emotional distress. Loneliness can have detrimental effects on mental and physical wellbeing, expressed as an increased risk of morbidity and mortality. Higher rates of loneliness are observed in patients suffering from chronic health conditions, mental health conditions, cardiovascular problems, and neurodivergent populations, including autistic individuals. While the link between poor health and loneliness is established, the identification of relevant underlying mechanisms is a difficult endeavor. In this narrative review, we provide an overview of published research and related literature describing the manifold interactions between loneliness, affective symptomatology, neural and embodied processing relevant to physical health, mental health, and neurodiversity. We propose a framework that can inform the identification of psychophysiological mechanisms underlying the link between loneliness and affective symptomatology that may represent interventional targets to mitigate the associated cycle of biopsychosocial morbidity.